2017
DOI: 10.1038/pr.2017.116
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record-based predictive models for acute kidney injury screening in pediatric inpatients

Abstract: Background Acute kidney injury (AKI) is common in pediatric inpatients and associated with increased morbidity, mortality, and length of stay. Early identification can reduce severity. Methods To create and validate an electronic health record (EHR)-based AKI screening tool, we generated temporally distinct development and validation cohorts using retrospective data from our tertiary care children’s hospital, including children 28 days through 21 years old with sufficient serum creatinine measurements to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…AKI is often preventable and reversible. Computerized provider order entry intervention (25,26), electronic alerts (27,28), risk assessment toolkits (29), and care bundles (30) are being increasingly implemented to facilitate early detection, improve care processes, prevent worsening of patient outcomes, and reduce health-care resource utilization in different settings. For example, identified AKI risk factors can be used to generate predictive models to screen individual patients for AKI in specific settings, such as intensive care unit (ICU) and non-ICU settings (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI is often preventable and reversible. Computerized provider order entry intervention (25,26), electronic alerts (27,28), risk assessment toolkits (29), and care bundles (30) are being increasingly implemented to facilitate early detection, improve care processes, prevent worsening of patient outcomes, and reduce health-care resource utilization in different settings. For example, identified AKI risk factors can be used to generate predictive models to screen individual patients for AKI in specific settings, such as intensive care unit (ICU) and non-ICU settings (29).…”
Section: Discussionmentioning
confidence: 99%
“…Computerized provider order entry intervention (25,26), electronic alerts (27,28), risk assessment toolkits (29), and care bundles (30) are being increasingly implemented to facilitate early detection, improve care processes, prevent worsening of patient outcomes, and reduce health-care resource utilization in different settings. For example, identified AKI risk factors can be used to generate predictive models to screen individual patients for AKI in specific settings, such as intensive care unit (ICU) and non-ICU settings (29). Considering the increase in the incidence of CA-AKI, further studies could be useful in determining the application of risk factors identified in our analysis (patient-related underlying diseases, acute illnesses, and nephrotoxic medicines) in the development of e-alert systems and risk assessment tools for pediatric patients who are at risk for AKI in outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, once the AKI has resolved, the ability to identify these patients accurately, allows them to be "tagged" and followed whether they developed ESRD, CKD, or experienced full recovery. potential predictors were chosen a priori based upon their association with AKI in prior studies (40)(41)(42)(43)(44)(45). While certainly statistically sound, these approaches do not take full advantage of big data informatics methods.…”
Section: Predicting Acute Kidney Injury Eventsmentioning
confidence: 99%
“…The EHR-based risk prediction models for AKI have been described. (28) In brief, using EHR data from pediatric ICU patients, we developed and validated a statistical model to predict AKI risk during ICU hospitalization based on 10 characteristics (age, high-risk nephrotoxins, moderate risk nephrotoxins, total number of medications, platelet count, red blood cell distribution width, phosphorus, transaminases, pH, and hypotension). A second model was generated for pediatric ward patients using 8 characteristics (as above, without pH or hypotension).…”
Section: Acute Kidney Injury Risk Prediction Modelsmentioning
confidence: 99%